Retirement Transitions and Anxiety among Teachers - Saligram, Deepthi; Murthy, C.G. Venkatesha (JOURNAL OF INDIAN EDUCATION, 2021)
The purpose of the present study is to assess the level of anxiety among pre-retiree and retired teachers at different stages of retirement among 200 teachers (100 pre-retiree and 100 retired) from educational institutions (Kendriya Vidyalayas, State Government Schools, PU and Degree Colleges) across Bangalore, Karnataka. The State Trait Anxiety Test (STAT) by Sanjay Vohra (1993) was used to assess ‘anxiety’ among these teachers. The analysis showed a significant difference between pre-retiree and retired teachers with higher level of anxiety among pre-retiree teachers. While, there was no significant difference in the level of anxiety among the two groups of pre-retiree (6 months and 3 years) and retired (6 months and 3 years) teachers within. Implications are discussed.